2005
DOI: 10.1007/s00204-005-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interleukins 2 and 12 on the levels of granzyme B and perforin and their mRNAs in tributyltin-exposed human natural killer cells

Abstract: Natural killer (NK) cells are a subset of lymphocytes that are capable of killing tumor cells, virally infected cells and antibody coated cells. Tributyltin (TBT) is a toxic chemical used for various industrial purposes such as: slime control in paper mills, disinfection of circulating industrial cooling waters, anti-fouling agents, and the preservation of wood. TBT can be found in edible items such as fish. A previous study showed that a 1 h exposure of NK cells to TBT caused persistent inhibition of NK-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Therefore, the chronic negative effects of TBT, even in low concentrations, are worrisome. Indeed, a wide variety of organisms are affected by this compound (Fent, 1996; Bekri and Pelletier, 2004; Sousa et al, 2005; Thomas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the chronic negative effects of TBT, even in low concentrations, are worrisome. Indeed, a wide variety of organisms are affected by this compound (Fent, 1996; Bekri and Pelletier, 2004; Sousa et al, 2005; Thomas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the decreases in granzyme B and perforin expression seen with exposures to TBT (Thomas et al, 2004; and Thomas et al, 2005) cannot be explained by TBT-induced activation of p44/42, in contrast to the TBT-induced effects on lytic function. This indicates that other TBT-induced changes, such as p38 activation (Aluoch and Whalen, 2005; Aluoch et al,2006) or increases in cytosolic calcium ion (Lane et al, 2009), may be responsible for the decreases seen in these proteins.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies indicated that exposure to TBT decreases the lytic function of NK cells (Dudimah et al, 2007; Whalen et al, 1999), decreases their expression of cytolytic proteins (granzyme B and perforin) (Thomas, et al, 2004; Thomas et al, 2005), and activates mitogen activated protein kinases (MAPK), including p44/42 (Aluoch and Whalen, 2005; Aluoch et al, 2006; Aluoch et al, 2007). TBT-induced loss of NK function could leave exposed individuals with an increased risk of viral infection and /or tumor formation.…”
Section: Introductionmentioning
confidence: 99%
“…From all the results of the key reaction cascade detailed above, we demonstrated that we could tune the reaction path by selecting the right metal: stannylated derivative 11a followed path II, whereas silylated derivative 11b followed path I. Most importantly, to avoid the use of organotin due to its toxicity, we successfully forced the desired reaction (path II) even with silylated substrate 11b by adding n -Bu 4 NCl to rapidly cleave the C−Si bond as soon as the formamide was activated (entry 5). Adduct 12 was obtained as the major diastereomer in an excellent yield.…”
mentioning
confidence: 99%